Sodium glucose co-transporter inhibitors for the management of diabetes mellitus: an opinion paper from the Endocrine and Metabolism Practice and Research Network of the American College of Clinical Pharmacy. (2nd September 2015) - Clements, Jennifer N.; Whitley, Heather P.; D'Souza, Jennifer J.; Gross, Benjamin; Hess, Rick; Reece, Sara; Gentry, Chad; Shealy, Kayce
Abstract: Type 2 diabetes mellitus (T2DM) carries a high prevalence in the United States and worldwide. Therefore, the number of medication classes being developed and studied has grown. The individualized management of diabetes is accomplished by evaluating a medication's efficacy, safety, and cost, along with the patient's preference and tolerance to the medication. Sodium glucose co-transporter 2 inhibitors are a new therapeutic class indicated for the treatment of diabetes and have a unique mechanism of action, independent of beta-cell function. The first agent approved by the Food and Drug Administration (FDA) was canagliflozin in March 2013. Two agents – dapagliflozin and empagliflozin – were FDA-approved in January and July 2014, respectively. A clear understanding of the new class is needed to identify its appropriate use in clinical practice. Members of the American College of Clinical Pharmacy Endocrine and Metabolism Practice and Research Network reviewed available literature regarding this therapeutic class. The article addresses the advantages, disadvantages, emerging role, and patient education for sodium glucose co-transporter 2 inhibitors. Key limitations for this article include limited access to clinical trial data not published by the pharmaceutical company and limited data on products produced outside the United States.